Pengembangan Kompetensi Sosial Pendidik Pendidikan Agama Islam dalam Praktik Interaksi Edukatif di Sekolah - Fikri, Muhammad; Fadriati, Fadriati; Suryana, Ermis (Lembaga Yasin AlSys, 2025)
Although teachers’ social competence has received attention in various educational studies, research that specifically highlights the development of the social competence of Islamic Religious Education (PAI) teachers within educational interactions grounded in Islamic values in school settings remains limited. This study aims to explore the forms of social competence demonstrated by PAI teachers, the strategies employed to develop it, and the challenges encountered in building effective and humanistic educational interactions in schools. The study adopts a qualitative approach with a case study design, involving ten PAI teachers selected through purposive sampling based on their experience and active involvement in PAI teaching. Data were collected through in-depth interviews, participatory observations, and documentation, and were systematically analyzed using thematic analysis techniques. The findings show that PAI teachers’ social competence is reflected in their ability to engage in dialogical interpersonal communication, their social sensitivity and empathy toward students, and their social role modeling in daily attitudes and behavior. The development of this competence is pursued through continuous reflection, personal approaches, and collaboration with school stakeholders, despite structural challenges such as time constraints and the complexity of students’ characteristics. These findings contribute to the development of teacher social competence theory by underscoring the importance of integrating Islamic values into educational interaction practices, while also broadening understanding of the role of PAI teachers as agents of moral and social development in schools. The study concludes by emphasizing the urgency of strengthening the social competence of PAI teachers to improve the quality of Islamic Religious Education, and encourages schools and education policymakers to design more holistic and sustainable teacher professional development programs. The implications of this research include theoretical contributions to enriching the literature on Islamic education and practical implications for educational institutions in enhancing the quality of value-based learning, as well as opening avenues for further research on the impact of PAI teachers’ social competence on learning outcomes and students’ character formation.